Evaluating bowel movements, self‐initiations, and problem behavior with the emergence of urinary continence. Issue 3 (12th April 2021) - Perez, Brandon C.; Morris, Samuel L.; Bacotti, Janelle K.; Vollmer, Timothy R.
Abstract : Much of the research evaluating toilet training interventions for children with ASD has focused on urinations as the primary dependent variable. As a result, the effects that toilet training interventions targeting urinations may have on other related dependent variables remains unclear. We conducted a retrospective analysis of data obtained by Perez et al. (2020), who evaluated the effects of a treatment package on urinary continence in children with ASD. We examined the relation between the emergence of urinary continence and multiple nontargeted dependent variables: bowel movements, self‐initiation correspondence, percentage of appropriate urinations that were self‐initiated, self‐initiation rate, and problem behavior. Results showed that improvements in urinary continence were strongly correlated with improvements in all nontargeted dependent variables. Implications for future research and clinical practice are discussed.